Spermatozoa motility in bivalves: Signaling, flagellar beating behavior, and energetics - Boulais, Myrina; Demoy-schneider, Marina; Alavi, Sayyed Mohammad Hadi; Cosson, Jacky (Theriogenology, 2019)
Though bivalve mollusks are keystone species and major species groups in aquaculture production worldwide, gamete biology is still largely unknown. This review aims to provide a synthesis of current knowledge in the field of sperm biology, including spermatozoa motility, flagellar beating, and energy metabolism; and to illustrate cellular signaling controlling spermatozoa motility initiation in bivalves. Serotonin (5-HT) induces hyper-motility in spermatozoa via a 5-HT receptor, suggesting a serotoninergic system in the male reproductive tract that might regulate sperm physiology. Acidic pH and high concentration of K+ are inhibitory factors of spermatozoa motility in the testis. Motility is initiated at spawning by a Na+-dependent alkalization of intracellular pH mediated by a Na+/H+ exchanger. Increase of 5-HT in the testis and decrease of extracellular K+ when sperm is released in seawater induce hyperpolarization of spermatozoa membrane potential mediated by K+ efflux and associated with an increase in intracellular Ca2+ via opening of voltage-dependent Ca2+ channels under alkaline conditions. These events activate dynein ATPases and Ca2+/calmodulin-dependent proteins resulting in flagellar beating. It may be possible that 5-HT is also involved in intracellular cAMP rise controlling cAMP-dependent protein kinase phosphorylation in the flagellum. Once motility is triggered, flagellum beats in asymmetric wave pattern leading to circular trajectories of spermatozoa. Three different flagellar wave characteristics are reported, including “full”, “twitching”, and “declining” propagation of wave, which are described and illustrated in the present review. Mitochondrial respiration, ATP content, and metabolic pathways producing ATP in bivalve spermatozoa are discussed. Energy metabolism of Pacific oyster spermatozoa differs from previously studied marine species since oxidative phosphorylation synthetizes a stable level of ATP throughout 24-h motility period and the end of movement is not explained by a low ...